Pemberdayaan Masyarakat Desa Kerandon Dalam Pengembangan Akun Instagram Wisata Situs Keramat Cimandung - Pratama, Gama; Aisyah Dwi Putri, Nurrul; Riyanto, Akhmad; Abdul Syahid, Jundi; Muh Fadli; Jubaidah, Evien; Rohmah, Ainun; Sri Andini (LP3M IAIFA Kediri, 2024)
This study was conducted by KPM students of Universitas Islam Bunga Bangsa Cirebon as part of a community service program focused on the development of religious tourism in Kerandon Village, Talun District, Cirebon Regency. The program aimed to raise awareness and encourage community participation in promoting and preserving religious tourism in the area. Various activities were undertaken to publicize the religious sites, making them more well-known to a broader audience. Despite the limited time for program implementation, this challenge was addressed by creating successors who will continue the program in the future, ensuring its long-term impact on the local community. The findings show an increase in the number of visitors to the religious sites in Kerandon Village. Additionally, the program successfully heightened community awareness of the importance of cultural preservation and environmental protection around the sacred sites in the village. The active participation of the community in maintaining and promoting these sites indicates that the program has effectively achieved its goals. Through community empowerment, it is hoped that Kerandon Village will become a more attractive and well-preserved religious tourism destination, drawing visitors from both within and outside the region. Moreover, the increased awareness of the importance of preserving cultural heritage and the environment is expected to provide long-term positive effects on the development of religious tourism and the well-being of the Kerandon Village community.